PERSEDIAAN PADA PT REIKEN QUALITY TOOLS - Nurhalisa, Annisa; Meita, Iren (JURNAL MAHASISWA BINA INSANI, 2024)
This research aims to determine whether inventory procedures at PT Reiken Quality Tools are in accordance with accounting standards. The type of research used is field research using a qualitative approach and the sources of information in this research are the owner of PT Reiken Quality Tools and employees. This research uses a qualitative descriptive method where data is obtained from the interview process with the company and the collection of documents needed in the research which are then analyzed and comparing the research results with the theory that has been obtained. From the results of the research carried out, it can be seen that production inventory procedures are in accordance with accounting standards according to Mulyadi's book entitled Accounting Information Systems.